2023
DOI: 10.3390/ijms241411862
|View full text |Cite
|
Sign up to set email alerts
|

Intranasally Administered MSC-Derived Extracellular Vesicles Reverse Cisplatin-Induced Cognitive Impairment

Abstract: Neurotoxic side effects of chemotherapy include deficits in attention, memory, and executive functioning. Currently, there are no FDA-approved therapies. In mice, cisplatin causes long-term cognitive deficits, white matter damage, mitochondrial dysfunction, and loss of synaptic integrity. We hypothesized that MSC-derived small extracellular vesicles (sEVs) could restore cisplatin-induced cognitive impairments and brain damage. Animals were injected with cisplatin intraperitoneally and treated with MSC-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…One article of this Special Issue is dedicated to the therapeutic aspects of sEVs. Milutinovic et al investigated the role of sEVs isolated from human-bone-marrow-derived mesenchymal stromal cells (MSCs) in restoring cisplatin-induced cognitive impairments and brain damage [ 6 ]. The authors demonstrated in vivo that the intranasal delivery of MSC-derived sEVs reversed cisplatin-induced deficits in executive function and working as well as spatial memory.…”
mentioning
confidence: 99%
“…One article of this Special Issue is dedicated to the therapeutic aspects of sEVs. Milutinovic et al investigated the role of sEVs isolated from human-bone-marrow-derived mesenchymal stromal cells (MSCs) in restoring cisplatin-induced cognitive impairments and brain damage [ 6 ]. The authors demonstrated in vivo that the intranasal delivery of MSC-derived sEVs reversed cisplatin-induced deficits in executive function and working as well as spatial memory.…”
mentioning
confidence: 99%